2015
DOI: 10.1074/jbc.r115.650150
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Iron Metabolism by Hepcidin under Conditions of Inflammation

Abstract: Iron is a redox-active metal required as a cofactor in multiple metalloproteins essential for a host of life processes. The metal is highly toxic when present in excess and must be strictly regulated to prevent tissue and organ damage. Hepcidin, a molecule first characterized as an antimicrobial peptide, plays a critical role in the regulation of iron homeostasis. Multiple stimuli positively influence the expression of hepcidin, including iron, inflammation, and infection by pathogens. In this Minireview, I wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 102 publications
4
105
0
4
Order By: Relevance
“…Additionally, hepcidin/ferroportin‐dependent mechanisms mean that iron deficient individuals generally absorb a higher proportion of ingested iron, and gastrointestinal absorption may be further enhanced in patients who are actively bleeding, or with cirrhotic liver diseases . In contrast, patients with chronic and/or inflammatory disease states with inappropriately elevated hepcidin have more limited gastrointestinal iron absorption, irrespective of ingested iron doses …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, hepcidin/ferroportin‐dependent mechanisms mean that iron deficient individuals generally absorb a higher proportion of ingested iron, and gastrointestinal absorption may be further enhanced in patients who are actively bleeding, or with cirrhotic liver diseases . In contrast, patients with chronic and/or inflammatory disease states with inappropriately elevated hepcidin have more limited gastrointestinal iron absorption, irrespective of ingested iron doses …”
Section: Discussionmentioning
confidence: 99%
“…65 In contrast, patients with chronic and/or inflammatory disease states with inappropriately elevated hepcidin have more limited gastrointestinal iron absorption, irrespective of ingested iron doses. 53,66…”
Section: Discussionmentioning
confidence: 99%
“…9 It is thought that hepcidin synthesis is influenced by cytokines such as interleukin 6 (IL 6), which promotes iron uptake by cells of the innate immune system. 10 Similar to hepcidin, the synthesis of CRP by hepatocytes is 5 driven by circulating IL 6. 11 In addition, albumin, although it is not directly involved in iron transport, is quantitatively the most important circulating binding protein, and is itself a negative acute phase protein commonly measured in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocytes, it has been well‐documented that inflammation induces hepcidin gene expression via the interleukin‐6 (IL‐6)/signal transducer and activator of transcription 3 (STAT3) pathway, via iron sensing through the transferrin receptor 2 (TfR2)/human hemochromatosis protein (HFE), and the bone morphogenetic protein (BMP)/hemojuvelin (HJV)/SMAD (a small mothers of decapentaplegic protein) pathways, and downregulated by erythroferrone (ERFE) ‐dependent and ‐independent mechanisms . Recent studies have also demonstrated that hepcidin expression can be upregulated by progesterone and mifepristone, two steroid hormones, through cell surface protein progesterone receptor membrane component‐1, transforming growth factor β1, SMAD1/5/8‐independent signaling by activin B, oxidases such as NADPH‐dependent oxidase 4 or artificially overexpressed urate oxidase (UOX), IL‐1β via inducing CCAAT enhancer‐binding protein δ (C/EBPδ) expression, peroxiredoxin‐2 which is a supporter for STAT3 transcriptional activity, fibroblast growth factor‐encoding gene, and downregulated by the immunophilin FKBP12 (FK506‐binding protein 1A) via binding with BMP type I receptor ALK2, cystathionine β‐synthase, TfR1, and matriptase‐2 …”
Section: Hepcidin and The Treatment Of Neurodegenerative Disordersmentioning
confidence: 99%